Structure and photoluminescence of magnesium germanate containing tetravalent manganese as activating cation - Larissa Nolding Nicolau; Ada López; Lilian Pantoja Sosman; Sandra da Silva Pedro (Vetor)
The aim of the current study is to present the acetate method synthesis of magnesium germanate (Mg2GeO4) compound containing Mn4+ as activating cation for optical transitions. The crystalline structure of this compound was investigated through X-ray diffraction measurements in association with the Rietveld method, which confirmed the formation of the intended compound. Photoluminescence spectroscopy measurements have shown emission in the red region. The emission spectrum under 287 nm excitation presented an intense peak at 660 nm, followed by several structures. Optical transitions were identified and confirmed Mn4+ occupation in octahedral symmetry. Crystal field parameter Dq and Racah parameters B and C, were calculated based on optical spectra. Emission lifetime was 2.8 ms, and it was compatible to the spin-forbidden electronic transition 2E(2G) → 4A2( 4F) attributed to the emission at 660 nm. The current findings pointed out that the sample was successfully synthesized, and that its optical properties can be used in devices that operate with emission in the red range of the visible spectrum.